How to win friends & influence people - Carnegie, Dale, 1888-1955; MacMillan, Andrew (New York : Simon and Schuster Audio, 1988)
For over 60 years the rock-solid, time-tested advice this book has carried thousands of now-famous people up the ladder of success in their business and personal lives. Learn: The six ways to make people like you; The twelve ways to win people to your way of thinking; The nine ways to change people without arousing resentment
Read by Andrew MacMillan
Keywords: Achievement motivation; Success; Psychology, Applied; Achievement